EVALUASI KINERJA LALU LINTAS PADA SIMPANG TAK SEBIDANG POLDA PALEMBANG DENGAN MIKROSIMULASI - Dimas Ariezky Susetyo (Politeknik Negeri Sriwijaya, 2023)
In 2023, Palembang city have four grade-separated intersections. One of the types of research is Polda intersection. The intersection has flyover infrastructure. Initially, this flyover was built in 2006 until 2008 to provide a solution to reduce congestion. Along with the growth of traffic in Palembang city until now, in fact it often causes congestion. The purpose of this research was to evaluate the performance of grade-separated intersection using the microsimulation PTV Vissim program. Performance evaluation is carried out by simulating traffic flow with current conditions. The results showed that microsimulation modelling at the Polda intersection Palembang experienced a queue of vehicles on the Demang Lebar Daun street along 297 meters/10 minutes during weekday peak hours and 217 meters/10 minutes during weekend peak hours. The results of evaluation and visual analysis can be used as references for the development of further research and optimization in the intersection area.